The difference of anti phenolic glycolipid-1 (PGL-1) immunoglobulin-M (IgM) level and nutritional intake in subclinical leprosy patients who reside at home and in the orphanage (Faculty of Medicine Universitas Indonesia, 2007)
Leprosy patients can be found in the orphanage, and ordinary house holds. The different living conditions in different places might cause differences in the environments, nutritional intake, and immunity, which in the end would affect the transmission of M. leprae. The aim of this study was to find out the difference in anti PGL-1 IgM level and nutritional intake between sub-clinical leprosy patients residing at home with their families and those living in the orphanage. This cross-section observational study was done in Semarang, Central Java, Indonesia. Thirty one sub-clinical leprosy patients living in an orphanage and 30 sub-clinical leprosy patients living at home were included in this study. Venous blood was taken from all of the subjects, the level of anti PGL-1 IgM was measured, and daily nutrient intake was analyzed. Differential test between the 2 groups was performed using independent t-test or Mann Whitney test, when the distribution was not normal. There was significant differences (P < 0.05) in the level of anti PGL-1 IgM, protein, zinc, and vitamin C intake between the 2 groups. (Med J Indones 2007;16:233-6)